The Performance of the Fama-French Five-Factor Model During High and Low Volatility Regimes : Empirical Evidence from Nordic Countries between 2005 and 2024 - Plusisaari, Jami (My University, 2025)
This thesis explores how the Fama and French Five-Factor Model performs under shifting market conditions in the Nordic stock markets. Recognizing that asset pricing models often behave differently across economic environments, the study examines whether the model’s explanatory power and factor performance change during periods of high and low market volatility. The analysis focuses on the stock exchanges of Finland, Sweden, Denmark and Norway, using monthly data spanning from 2005 to 2024. Using rolling 12-month regressions on six portfolios constructed from firm size and book-to-market characteristics, the study examines how well the five-factor model explains excess returns in contrasting volatility regimes. Beyond adjusted R-squared values, the analysis assesses the statistical significance of the estimated factor coefficients and examines multicollinearity through variance inflation factors. The market environment is segmented into high- and low-volatility periods based on the annual standard deviation of monthly market returns, enabling a dynamic and granular assessment of factor performance across regimes. While the results do not offer a single straightforward conclusion, the empirical evidence indicates that the model’s explanatory power improves during high-volatility periods, especially in portfolios composed of small-cap stocks. The market factor is the most consistently significant across all regimes, reinforcing its central role in pricing excess returns. The size factor shows regime-dependent relevance, becoming more significant in small-cap portfolios depending on the volatility environment. In contrast, the value factor demonstrates mixed behavior, showing greater relevance in large-cap portfolios during stable periods. Profitability and investment factors contribute less overall, with limited significance in most portfolios and regimes. Overall, aside from the market factor, the number of statistically significant estimates across other factors remains relatively low, and indications of multicollinearity further complicate the interpretation of individual factor effects. These findings suggest that while the five-factor model provides a valuable framework, its effectiveness is influenced by both market volatility and portfolio composition. The results underline the need for adaptive asset pricing models that respond to changing market conditions and reflect the complexity of real-world financial systems in diverse financial contexts.

Taloudellisen ympäristön on näytetty vaikuttavan hinnoittelumallien toimivuuteen. Tässä tutkimuksessa selvitetään, muuttuvatko mallin selitysvoima ja faktoreiden vaikutukset korkean ja matalan volatiliteetin jaksoissa. Aineisto kattaa Suomen, Ruotsin, Tanskan ja Norjan pörssit, ja perustuu kuukausittaisiin havaintoihin vuosilta 2005–2024. Tutkimuksessa käytetään liikkuvia 12 kuukauden regressioita kuudelle portfoliolle. Portfoliot on rakennettu yhtiökoon ja tasepohjaisen arvostuksen perusteella. Mallin toimivuutta arvioidaan vertaamalla korjattua selitysastetta, faktoreiden tilastollista merkitsevyyttä ja multikollineaarisuutta, jota mitataan VIF -arvoilla. Markkinaympäristö on jaettu korkean ja matalan volatiliteetin jaksoihin kuukausittaisten tuottojen vuotuisen vaihtelun perusteella. Tämä mahdollistaa faktoreiden toiminnan yksityiskohtaisemman tarkastelun eri tilanteissa. Yksiselitteistä johtopäätöstä ei saada, mutta tulokset viittaavat siihen, että mallin selitysvoima paranee korkean volatiliteetin aikana. Tämä näkyy erityisesti portfolioissa, joissa on paljon pienyhtiöitä. Markkinafaktori on johdonmukaisesti tilastollisesti merkittävin tekijä kaikissa jaksoissa. Kokofaktori näyttää reagoivan markkinatilanteeseen ja korostuu pienyhtiöissä merkitsevyydellään. Arvotekijän merkitys vaihtelee, mutta näyttää kasvattavan merkitsevyyttä suurten yhtiöiden portfolioissa vakaassa markkinassa. Kannattavuus- ja investointifaktoreiden vaikutus jää vähäiseksi, eikä tilastollista merkitsevyyttä yleensä saavuteta. Markkinafaktoria lukuun ottamatta tilastollisesti merkitseviä faktoreiden kertoimia esiintyy vain vähän. Lisäksi havaittu multikollineaarisuus vaikeuttaa yksittäisten faktoreiden tulkintaa. Tutkimus osoittaa, että viisifaktorimalli toimii eri tavoin eri tilanteissa. Sen käyttökelpoisuus riippuu markkinatilanteesta ja portfolion rakenteesta. Tulokset korostavat joustavien hinnoittelumallien tarvetta. Mallien on pystyttävä reagoimaan markkinoiden muutoksiin ja kuvaamaan paremmin rahoitusjärjestelmien toimintaa erilaisissa taloudellisissa ympäristöissä.
Keywords: Fama & French, five-factor model, asset pricing, Nordic stock markets, volatility regimes, Fama & French, viisifaktorimalli, osakkeiden hinnoittelu, pohjoismaiset osakemarkkinat, volatiliteettijaksot